(untitled) (Applied Biological Research, 2023)
Little millet, having a significant nutritional value, has not been exploited to its true potential so remains underutilized. The molecular relatedness analysis of available genotypes is a crucial step in crop improvement and germplasm conservation of millets. The present study evaluated genetic relatedness among 16 little millet genotypes, collected from Dang region of Gujarat (India), using random amplified polymorphic DNA (RAPD) markers. Initially, a total of 120 RAPD primers were screened, of which only 25 RAPD primers produced distinct bands so were used for further analysis. RAPD analysis with selected 25 decamer primers amplified a total of 193 bands with amplicon sizes in between 50-2392 bp. There were 126 polymorphic bands (64.25%) with mean polymorphic bands of 5.04 per primer. The maximum marker index of 41.25,maximum polymorphic information content of 0.59 and maximum RAPD primer index of 5.69 were recorded in primers OPC-13, OPC-17, and OPA-12, respectively. The RAPD primers OPA-12, OPC-13, and OPC-17 proved most efficient for genetic relatedness analysis in little millet. The Jaccard’s similarity coefficient among the genotypes was in the range of 0.53 to 0.98 revealia moderate genetic diversity among the available genotypes. The dendrogramdivided 16 genotypes of little millet into two major clusters and further sub clusters, demonstrating that RAPD technique was effective to distinguish the studied genotypes. The dendrogram and PCoA analysis revealed that genotypes WV-151 and WV-161 were highly diverse. These genotypes along with genetic relatedness established in this study can be exploited in future little millet improvement programs with conventional and molecular breeding methods.